Perspectives on abortion in Ecuadorian gynecologists and obstetricians - Condori Bueno, Alfredo Agapito (2017)
After reviewing an article published in this Peruvian Review Of Obstetrics and Gynecology, known as' Knowledge, attitudes and Practices on abortion in a sample of gynecological obstetricians Of Ecuador '(1), we wish to make some observations that we believe Relevant. The mentioned article indicates to be a transversal study Analytical and correlational descriptive analysis. Nevertheless, It is known that studies are considered analytical "when their purpose Is to evaluate an alleged causal relationship between a factor ... and an effect, Response or outcome "(2), which is not observed in the study mentioned. It is said to be correlational; However in this respect Sampieri points out: "These types of studies are intended to measure the degree of relationship That exists between two or more concepts or variables, each measure And then quantify and analyze the linkage. Such correlations Are based on hypotheses put to the test ", which has not been Account (3). The article in question corresponds to a type study Descriptive study.